Comparison of dysplastic fundic gland polyps in patients with and without familial adenomatous polyposis. Issue 7 (24th March 2018) - Straub, Shana F; Drage, Michael G; Gonzalez, Raul S
Abstract : Aims: Dysplastic fundic gland polyps (d‐FGPs) typically arise in patients with familial adenomatous polyposis (FAP) but may occur in non‐syndromic patients. They rarely become malignant, but their significance is unclear, especially in non‐syndromic patients. We aimed to compare d‐FGPs in patients with and without FAP, using clinicopathologic findings and β‐catenin immunohistochemistry (IHC). Methods and results: We identified 124 fundic gland polyps with low‐grade dysplasia (LGD) or high‐grade dysplasia (HGD) or indefinite for dysplasia (IFD) from 66 patients (27 with FAP; 39 non‐syndromic). We recorded patient sex, age at first d‐FGP, time until subsequent d‐FGP (if any), history of non‐gastric cancer (no patients had gastric cancer), proton‐pump inhibitor use, and the presence of Helicobacter pylori . β‐Catenin IHC was performed on cases with available blocks. The mean age at d‐FGP diagnosis was 31 years for FAP patients and 61 years for non‐syndromic patients ( P < 0.0001). Sixteen FAP patients (59%) developed at least one subsequent d‐FGP, as compared with 10 (27%) non‐syndromic patients ( P = 0.0099). The median time between d‐FGP detection was 11.5 months in FAP patients and 7 months in non‐syndromic patients ( P = 0.82). Six FAP patients (22%) and 17 non‐syndromic patients (44%) had non‐gastric malignancies ( P = 0.11). β‐Catenin IHC showed nuclear positivity in 14 of 112 (13%) d‐FGPs: 12 of 94 with LGD, two of three with HGD, and none of 15 with IFD polyps. Conclusions: Familial adenomatous polyposis patients develop d‐FGPs earlier and more often develop additional ones than non‐syndromic patients. d‐FGPs in FAP and non‐syndromic patients have similar low rates of β‐catenin nuclear IHC positivity. FAP and non‐syndromic patients developed non‐gastric cancers at similar rates, suggesting that d‐FGPs may portend a general increased risk of carcinogenesis in non‐syndromic patients.